Production of Omega-3 Triacylglycerol concentrates using a new food grade immobilized Candida antarctica Lipase B - J Kralovec; W Wang; Colin Barrow (2010)
Triacylglycerol concentrates of eicosapentaenoic and docosahexaenoic omega-3 fatty acids were synthesized either via transesterification or esterification of glycerol with the corresponding ethyl ester or free fatty acid concentrates, respectively. A newly developed food grade immobilized Candida antarctica lipase Β system using an Amberlite FPX-66 hydrophobic matrix, was compared with a commercially available non-food grade commercial system, for their ability to catalyze these reactions. For either system, the transesterification required higher temperature (90◦C) than esterification (70°C) to achieve maximum triacylglycerol yields. The newly developed immobilized system efficiently catalyzes the esterification of free fatty acids with glycerol and differs from the existing commercial system in that it is food grade and has a more uniform and larger particle distribution. The new system significantly improves flow in a packed bed reactor, enabling multiple reuse of the catalyst for up to 80 repeats.